Constraining the nature of the accreting binary in CXOGBS J174623.5−310550. Issue 2 (5th June 2019) - Torres, M A P; Repetto, S; Wevers, T; Heida, M; Jonker, P G; Hynes, R I; Nelemans, G; Kostrzewa-Rutkowska, Z; Wyrzykowski, L; Britt, C T; Heinke, C O; Casares, J; et al.
ABSTRACT: We report optical and infrared observations of the X-ray source CXOGBS J174623.5−310550. This Galactic object was identified as a potential quiescent low-mass X-ray binary accreting from an M-type donor on the basis of optical spectroscopy and the broad H α emission line. The analysis of X-shooter spectroscopy covering three consecutive nights supports an M2/3-type spectral classification. Neither radial velocity variations nor rotational broadening is detected in the photospheric lines. No periodic variability is found in I - and r ′-band light curves. We derive r ′ = 20.8, I = 19.2, and K s ≈ 16.6 for the optical and infrared counterparts with the M-type star contributing ${≈ }90{{\ \rm per\ cent}}$ to the I -band light. We estimate its distance to be 1.3–1.8 kpc. The lack of radial velocity variations implies that the M-type star is not the donor star in the X-ray binary. This could be an interloper or the outer body in a hierarchical triple. We constrain the accreting binary to be a ≲2.2 h orbital period eclipsing cataclysmic variable or a low-mass X-ray binary lying in the foreground of the Galactic bulge.